Late Holocene sedimentation and hydrologic development in a shallow coastal sinkhole on Great Abaco Island, The Bahamas - Kovacs, Shawn E.; van Hengstum, Peter J.; Reinhardt, Eduard G.; Donnelly, Jeffrey P.; Albury, Nancy A. (Quaternary International, 2013)
It remains poorly understood how sea level drives environmental change and hydrographic development in coastal karst basins (underwater caves, sinkholes, blueholes, etc.) over millennial timescales. It was previously hypothesized that coastal karst basins (CKBs) transition from vadose, to littoral, then anchialine, and finally submarine environments as sea-level rise inundates coastal karst landscapes, but the initial flooding event of CKBs remains challenging to sample. Runway Sinkhole hosts a modern anchialine ecosystem located ∼225 m from Great Abaco Island coastline in The Bahamas, and its shallow water depth (∼1.8 mbsl) permits an investigation into the early environmental evolution and hydrographic development in a CKBs after inundation by sea-level rise. Four sediment cores were collected from Runway Sinkhole, and late Holocene environmental change was reconstructed with benthic foraminiferal paleoecology, organic matter geochemistry (OM%, δ13Corg, and C:N), X-radiography, and radiocarbon dating. Despite some uncertainties associated with the chronology, it appears that Holocene sea-level rise initially flooded Runway Sinkhole and created a littoral environment at least by ∼3.9 ka, whereafter a detrital peat deposit accumulated in the sinkhole. This detrital peat had a high organic matter content (mean 88%), a δ13Corg value indicative of organic matter derived from C3 plants including mangroves (−28‰), and an unknown calcareous microfossil suggestive of a non-marine habitat in the sinkhole. A shift to carbonate sand deposition, organic matter with more marine-influenced δ13Corg values (−23‰), and expansion of euryhaline (Bolivina striatula, Elphidium poeyanum, and Triloculina bermudezi) and anchialine (Physalidia simplex and Conicospirillina exleyi) benthic foraminifera at ∼1.2 ka marks the onset of modern anchialine environmental conditions at the sediment–water interface (∼1.8 mbsl). These results suggest that relative sea-level rise in the Bahamas forced environmental change in Runway sinkhole at ∼1.2 ka, and indicate that peat deposits in coastal sinkholes must be verified as in-situ before being utilized as sea-level indicators.